PENGARUH KOMPOSISI MEDIA TUMBUH TERHADAP PERTUMBUHAN SEMAI KEMIRI (ALEURITES MOLUCCANA WILD) - Arman, Arman; Muslimin, Muslimin; Rahmawati, Rahmawati (Jurnal Warta Rimba, 2015)
Pecans (Aleurites molucanna Wild) is one of the farming commodities potential to grow. It is known as cooking spice seeds, industry material such as paint, furnish, soap, candle ingredient, wood preserve, and cosmetics. The research aims to find out the influence of the exact grow media composition toward pecans seedling grow ((Aleurites molucanna Wild). It was conducted from November 2013 to March 2014 at Permanent Building for Seedling of Tadulako University, Palu, Central Sulawesi Province. The method employed was Complete Random Design with six treatments, namely: MO= Soil (control), M1= Soil + Cow dung fertilizer + paddy dust charcoal (1:1:1), M2= Soil + Cow dung fertilizer + wood powder, M3= Soil + paddy dust charcoal (2:1), M4= Soil + wood powder, and M5= Soil + cow dung fertilizer (2:1). The parameter observed was height, diameter, leaf number, wet weight, dry weight of pecans seedling. The smallest real difference testing was done to find out the difference treatment. The result indicates that the difference grow media really influence toward height, diameter and leaf number. The smallest real difference testing result of all treatments show that grow media M5 is the best. Key words: Growth media, Pecans Grow